Evidence of Viremia in Dairy Cows Naturally Infected with Influenza A Virus, California, USA - Jason Lombard; Chloe Stenkamp-Strahm; Brian McCluskey; Blaine Melody (Emerging Infectious Diseases, 2025)
We confirmed influenza A virus (IAV) by PCR in serum from 20 cows on 3 affected dairy farms in California, USA. Our findings indicate the presence of viremia and might help explain IAV transmission dynamics and shedding patterns in cows. An understanding of those dynamics could enable development of IAV mitigation strategies.